Answer:
109 is the 22nd term
Step-by-step explanation:
Ok it is so easy it is 489467000
Answer:
x³ + x² − 4x + 6 = 0
Step-by-step explanation:
Imaginary roots come in conjugate pairs. So if 1+i is a root, then 1−i is also a root.
(x − (-3)) (x − (1+i) (x − (1−i)) = 0
(x + 3) (x² − (1+i) x − (1−i) x + (1+i) (1−i)) = 0
(x + 3) (x² − x − ix − x + ix + 1 − i²) = 0
(x + 3) (x² − 2x + 2) = 0
x (x² − 2x + 2) + 3 (x² − 2x + 2) = 0
x³ − 2x² + 2x + 3x² − 6x + 6 = 0
x³ + x² − 4x + 6 = 0
Answer:
1.54cm 2. 112m 3. 576cm 4. 52ft
Step-by-step explanation:
Answer:
125
Step-by-step explanation:
x + y = 5
We need to have x^3 and y^3 in the expression, so cube both sides.
(x + y)^3 = 5^3
Expand the left side.
(x + y)(x + y)^2 = 125
(x + y)(x^2 + 2xy + y^2) = 125
x^3 + 2x^2y + xy^2 + x^2y + 2xy^2 + y^3 = 125
x^3 + 3x^2y + 3xy^2 + y^3 = 125
Now we need to separate x^3 + y^3.
x^3 + y^3 + 3x^2y + 3xy^2 = 125
We need to turn 3x^2y + 3xy^2 into 15xy.
Factor the GCF, 3xy, out of 3x^2y + 3xy^2.
x^3 + y^3 + 3xy(x + y) = 125
We know that x + y = 5, so substitute x + y with 5.
x^3 + y^3 + 3xy(5) = 125
x^3 + y^3 + 15xy = 125
Answer: 125